Design of a learning module for the deaf in a higher education institution using padlet - DeWitt, Dorothy; Alias, Norlidah; Ibrahim, Zainuddin; Ngu, Kee Shing; Mohd Rashid, Syar Meeze (2014)
which do not have facilities which cater to their needs. Padlet is a web application for interactions, may be used for communication among deaf students. This exploratory implementation study for the design of a learning module for deaf students used the Fuzzy Delphi technique among 27 experts. The prototype of the module was evaluated with data collected from observations and interviews of four deaf students. Findings indicate that Padlet could be used for communication among deaf students. However, further studies could be done to investigate its suitability in other contexts.